2022
DOI: 10.1371/journal.pntd.0010092
|View full text |Cite
|
Sign up to set email alerts
|

National mapping of schistosomiasis, soil-transmitted helminthiasis and anaemia in Yemen: Towards better national control and elimination

Abstract: Background Schistosomiasis (SCH) and soil-transmitted helminthiasis (STH) are known to be endemic in Yemen. However, the distribution of both diseases had not previously been assessed by a well-structured national mapping study covering all governorates. The main aim of this study was, therefore, to map the prevalence of SCH and STH in Yemen in order to better inform implementation of effective national control and elimination interventions. The assessment of the distribution of anaemia was also included as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…In terms of gender, the current study reported a positive (risk) correlation between s. mansoni and gender, with boys having greater prevalence rates of the infection than females despite the difference not being statistically signi cant. These were in line with numerous ndings from studies conducted in Yemen and other countries (20,38,39,40). However, other studies also found that males typically had greater prevalence rates of schistosomiasis than females, and this was explained by factors such as water contact habits or religious and cultural considerations (44,32,45,46,47).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In terms of gender, the current study reported a positive (risk) correlation between s. mansoni and gender, with boys having greater prevalence rates of the infection than females despite the difference not being statistically signi cant. These were in line with numerous ndings from studies conducted in Yemen and other countries (20,38,39,40). However, other studies also found that males typically had greater prevalence rates of schistosomiasis than females, and this was explained by factors such as water contact habits or religious and cultural considerations (44,32,45,46,47).…”
Section: Discussionsupporting
confidence: 89%
“…The risk of schistosomiasis in Taiz governorate, including Al-Shmaytin and Al-Mwaset districts, is classi ed as being moderate with a threshold of 10% to less than 50% for any type of schistosomiasis (20). However, the epidemiology of schistosomiasis following the mass drug administration (MDA) campaigns in the study districts is vague as a result of the ongoing con ict in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Schistosomiasis infections increase with age, peaking between the ages of 15 and 20 years, and severe infections occur in 5% to 10% of cases. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Schistosomiasis infections increase with age, peaking between the ages of 15 and 20 years, and severe infections occur in 5% to 10% of cases. 8 The progression of a colonic bilharzial polyp begins as a small submucosal granuloma with an increase in the surrounding mucous membrane proliferation. Then, it acquires a projection and protrudes within the bowel lumen due to its size, adjacent mucous membrane proliferation, and stool pressure.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recently published school-based national mapping survey, 31.6% and 54.2% of 332 districts of the country were identified as endemic for S. haematobium and S. mansoni, respectively (20).…”
Section: Introductionmentioning
confidence: 99%